1981
DOI: 10.1159/000119981
|View full text |Cite
|
Sign up to set email alerts
|

Dandy-Walker Malformation and Associated Cardiac Anomalies

Abstract: 2 patients with Dandy-Walker malformations (DWM) and cardiac anomalies are presented. The types of cardiac defects with septal involvement are suggestive of an early embryonic abnormality occurring before 6 weeks’ gestational age. This correlates with the postulated timing of the development of the DWM and suggests a complex developmental anomaly. Awareness of the associated systemic and central nervous system anomalies in patients with the DWM in regard to management and prognosis is emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The association between occipital meningoceles and Dandy-Walker syndrome was noted by Sutton [ 1 ] in the 1st reported case of the Dandv-Walker syndrome and has since then been well described [7,11,13,27,28]. Ten per cent of the patients in this series had associated occipital meningoceles.…”
Section: Discussionsupporting
confidence: 57%
“…The association between occipital meningoceles and Dandy-Walker syndrome was noted by Sutton [ 1 ] in the 1st reported case of the Dandv-Walker syndrome and has since then been well described [7,11,13,27,28]. Ten per cent of the patients in this series had associated occipital meningoceles.…”
Section: Discussionsupporting
confidence: 57%
“…Association of congenital heart disease and DWS is curious and has been reviewed by Olson et al [1981]. They noted that the most common congenital heart defect associated with DWS was some type of ventricu lar septal defect.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Hart et al [1972], 7 of 28 patients had systemic anomalies which included polydactyly/syndactyly and cleft palate. Others have added congenital renal cysts [Raimondi et al, 1981;D'Agostino et al, 1963], cardiac anomalies [Olson et al, 1981], diaphragmatic hernia [Fowler and Alexander, 1956], and Meckel's diverticulum [Taggert and Walker, 1942].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that it could be a disease of the Schwann cells with defective production of mye lin. However, these cells differentiate late, in the 14-16th week [22], while DWS starts already at the neural crest stage, in the first trimester, the 8-12th week or perhaps earlier [11].…”
Section: Discussionmentioning
confidence: 99%
“…<12 weeks of gestation [6]. The occur rence of cardiovascular anomalies points to the 3rd or 4th postovulatory week [11], and the warfarin exposure to the period preceding the 9th postovulatory week [6].…”
Section: Introductionmentioning
confidence: 99%